2014
DOI: 10.1007/s12028-013-9948-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Temperature Modulation for Fever After Intracerebral Hemorrhage

Abstract: Therapeutic normothermia is associated with increased duration of sedation, mechanical ventilation, and NICU stay, but is not clearly associated with improved discharge outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 12 publications
0
19
0
3
Order By: Relevance
“…Treatment of fever appears therefore reasonable but the optimal temperature management is still unclear 7 . Therapeutic normothermia failed to improve outcome in one trial 65 although treatment of fever did improve outcome in another 62 . It appears reasonable to minimize fever, and the role of targeted temperature management in ICH is still under investigation in a randomized clinical trial 66 .…”
Section: Acute Managementmentioning
confidence: 95%
“…Treatment of fever appears therefore reasonable but the optimal temperature management is still unclear 7 . Therapeutic normothermia failed to improve outcome in one trial 65 although treatment of fever did improve outcome in another 62 . It appears reasonable to minimize fever, and the role of targeted temperature management in ICH is still under investigation in a randomized clinical trial 66 .…”
Section: Acute Managementmentioning
confidence: 95%
“…However, neither therapeutic hypothermia nor normothermia was shown to improve outcome 6465 In a retrospective case–control study of patients with spontaneous ICH having two consecutive fevers ≥38.3°C despite acetaminophen administration, therapeutic normothermia was shown to be associated with increased duration of sedation, mechanical ventilation and Neuro-ICU length of stay without discharge outcome benefit 65. Normothermia or hypothermia should not be used after ICH except in the setting of clinical trials.…”
Section: Fever Controlmentioning
confidence: 99%
“…Two observational studies showed that hypothermia at 35 °C over 8–10 days had a favourable effect on peri-haemorrhagic oedema and ICP, with no benefit on neurological outcome [109, 110]. A case–control study using TTM at 37 °C found no effect on neurological outcome at ICU discharge, while the duration of mechanical ventilation and length of stay in the ICU was prolonged in patients treated with TTM [111]. The effect of hypothermia at 35 °C during 8 days is ongoing in patients with a large intra-cerebral haemorrhage (25–64 mL) (CINCH trial) [112].…”
Section: Resultsmentioning
confidence: 99%